Application of Health Belief Model and Social Cognitive Theory on the Use of Personal Protective Equipment among Workers at the Plywood Plant: Path Analysis Evidence from Lumajang, East Java - Bayu Putra Dewantara; Bhisma Murti; Vitri Widyaningsih (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Work safety and health is one of the efforts in preventing work accidents. One of the protective measures for factory workers is to use personal protective equipment (PPE) when carrying out work activities in the workplace. In the production of plywood wood dust exposure and formaldehyde can cause acute irritation to the skin, eyes and respiratory tract can also be associated with chronic respiratory symptoms. Awareness of the use of personal protective equipment needs to be instilled in every factory worker. This study aims to analyze the determinants of the behavior of the use of personal protective equipment in plywood factory workers.Subjects and Method: This study was conducted using a cross sectional research design. This was done at the plywood factory of PT Mustika Buana Sejahtera Lumajang, East Java, in December 2019. Sampling was carried out by 200 factory workers using simple random sampling. The dependent variable is the behavior of using personal protective equipment. The independent variables are motivation, training, attitude, outcome expectation, perceived benefits, vicarious experience, observational learning, obedience to regulations on the use of PPE, and reinforcement. Data were collected using a questionnaire. The data were analyzed by path analysis run on Stata 13.Results: The behavior of using personal protective equipment on workers directly increased with high motivation (b= 2.65; 95% CI= 1.36 to 3.95; p<0.001), observational learning (b= 3.82; 95% CI= 2.25 to 5.39; p<0.001), vicarious experience (b= 2.19; 95% CI= 0.90 to 3.48; p= 0.001), positive attitude (b= 2.38; 95% CI= 1.02 to 3.73; p= 0.001), obedient to the rules (b = 2.16 ; 95% CI= 0.83 to 3.49; p= 0.001), and experienced a strengthening (b= 2.64; 95% CI= 1.34 to 3.93; p <0.001). The use of PPE on workers was indirectly influenced by outcome expectation, perceived usefulness, and training.Conclusion: PPE use directly increases with high motivation, observational learning, vicarious experience, having a positive attitude, obeying the rules, and experiencing reinforcement. The possibility of using PPE indirectly is influenced by outcome expectation, perceived usefulness, and training.Keywords: PPE, factory workers, social cognitive theory, health belief modelCorrespondence: Bayu Putra Dewantara. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta, 57126, Jawa Tengah. Email: bayuputradewantara@gmail.com. Mobile: +6281352347536.Journal of Health Promotion and Behavior (2019), 4(4): 306-319https://doi.org/10.26911/thejhpb.2019.04.04.07